FBI Criminal Investigation Procedures On Finding A Missing Person In Gillian Flynn’s Gone Girl - Andy Amirudin; Wedi Rahmad Amran (Jurnal Ilmiah Pendidikan Scholastic, 2025)
The research entitled FBI Criminal Investigation Procedures on Finding a Missing Person in Gillian Flynn’s Gone Girl examines how the novel depicts the Federal Bureau of Investigation’s methods in solving Amy Dunne’s disappearance. The study explores how the narrative reflects real investigative practices, particularly regarding criminal evidence, missing person procedures, and underlying motives. The background emphasizes the role of crime fiction in shaping public views of law enforcement, while the purpose is to analyze the representation of FBI methods and assess their effectiveness in uncovering the mystery. This study uses a qualitative, descriptive-analytical approach, with Gone Girl as the primary text. Theories of criminal investigation, criminology, and narrative analysis support the interpretation. Data analysis involves categorizing textual evidence, identifying investigative patterns, and interpreting them through forensic and motive-based perspectives. The findings show that the novel illustrates the complexity of FBI missing person cases, highlighting physical and psychological evidence, systematic investigative steps, and the impact of hidden motives. Flynn blends authentic procedures with fictional exaggeration, enhancing narrative tension while emphasizing motive as central to crime. The portrayal reveals both the strengths and limitations of law enforcement in handling such cases.